Disability in employment equality law: A reappraisal of the reasonable accommodation duty and issues arising in its implementation. Issue 6 (December 2021) - Daly, Patrick; Whelan, Darius
This article re-considers the special features of the disability ground in EU equality law and raises questions as to whether the EU's Framework Equality Directive (Directive 2000/78) may be in need of fundamental reform. It argues that the 'Competence Defence' in the Directive could have been more strongly drafted, to prescribe more precisely the circumstances in which an individual may be found not to be competent to perform the post's essential functions. In the absence of a unified EU approach regarding the activation of the reasonable accommodation duty and an employer's knowledge as to disability or the need for reasonable accommodation, national positions are compared. A model whereby the provision for individuals with disabilities is carried out in a proactive as opposed to a reactive manner could reduce the need for the reasonable accommodation system. The possibility of increased state involvement in the provision of reasonable accommodation to employees has strong potential. It is proposed that the principle of Universal Design, as expressed in the Convention on the Rights of Persons with Disabilities, could be used to ensure that work environments are developed from the outset to be conducive to the needs of those with physical or psychosocial disabilities. The implications of such a major change are assessed.